Path interdependence in a dynamic two country Heckscher-Ohlin model - Beatriz Gaitan; Terry L. Roe (University of Bern, Department of Economics, 2007)
The closed economy neoclassical model predicts lung-run convergence in per-capita income. We show, within a neoclassical framework, that international trade among two countries differing only in their initial capital endowment generates long-run income differences. Our results suggests that trade creates opposite incentives to accumulate capital. Transitionally, the returns to investment with trade are smaller for countries initially less endowed with capital as when compared to their autarchic situation, while the reverse happens for those countries most endowed with capital. Thus, countries starting with relatively less (more) capital end, in the long run, with less (more) capital than in autarchy.
Keywords: O41; F43; F11; 330; International trade; Development; Multiple Equilibria; Faktorproportionentheorem; Pfadabhängigkeit; Zwei-Länder-Modell; Dynamisches Modell; Offene Volkswirtschaft; Neoklassik; Theorie